Human Factor on Software Quality: A Systematic Literature Review - Guveyi, Elcin; Aktas, Mehmet S.; Kalipsiz, Oya (SPRINGER INTERNATIONAL PUBLISHING AG, 2020)
Ensuring software quality is an important step towards a successful project. Since software development is a human-oriented process, it is possible to say that any factor affecting people will directly affect software quality and success. The aim of this study is to reveal which factors affect humans. For this purpose, we conducted a systematic literature review. We identified 80 related primary studies from the literature. We defined 7 research questions. For answering research questions, we extracted data from the primary studies. We researched human factors, methods for data collection and data analysis, publication types and years. Factors are grouped into 3 main groups: Personal factors, interpersonal factors, and organizational factors. The results show that personal factors are the most important category of human factors. It is seen that the most researched factors among personal factors are experience and education.
Keywords: Human factor; Software quality; Systematic literature review; Computer Science; Mathematics